A CONTRIBUTION TO BRACONIDAE, HYBRIZONTIDAE (HYMENOPTERA: ICHNEUMONOIDEA) AND STEPHANIDAE (HYMENOPTERA: STEPHANOIDEA) FROM THE SOUTH-WEST BALKANS (Acta Entomologica Serbica, 2010)
Below is a contribution of faunistic data of forty-two species belonging to the twelve braconid subfamilies and two species of the families Hybrizontidae and Stephanidae. Material has been collected from the South-West Balkans (Serbia, Montenegro, Former Yugoslav Republic of Macedonia and Greece). There were twenty species newly recorded for certain national faunas. One of the most interesting findings was Blacus (Ganychorus) striatus VAN ACHTERBERG, the micropterous species known from the Nearctic region of Alberta, Canada, VAN ACHTERBERG (1988).